The Significance of Normal Pretreatment Levels of CA125 (<35 U/mL) in Epithelial Ovarian Carcinoma - Joseph Menczer; Erez Ben-Shem; Abraham Golan; Tally Levy (Rambam Maimonides Medical Journal, 2015)
Objective: To assess the association between normal CA125 levels at diagnosis of epithelial ovarian carcinoma (EOC) with prognostic factors and with outcome.